Interfaces at internal chills in solidifying steel sections. (May 2019) - Monroe, Charles; Foley, Robin; Griffin, John; Gibbons, Sean; Saville, Alec
Abstract: Chills are used in the production of metal castings as a thermal aid to promote directional solidification in casted sections. This study will review microstructure and thermal circumstances of the internal chill interface where the chill is intended to be incorporated into the structure of the cast section. The conditions for interface coherency of cast steel sections from 25 to 50mm will be shown. Solidification proceeds away from the interface chill growing to a maximum thickness and then melting back to the original chill geometry. Furthermore, it is shown that promoting section solidification prior to the complete melting of the internal chill can lead to the formation of interfaces will be coherent across the chill and cast sections for compatible steel alloys. A computer model of the heat transfer and interface evolution show the possibility of using the coherent interface of internal chills in the design of other cast components.